Effectiveness of a Suggested Science Teaching Method in Light of Educational Implements of Surah Al-Kahf and Cognitive Equilibrium, in Developing Science Concepts and Self Regulation Skills - Al-zaaneen, Jamal (Jordan Journal of Educational Sciences, 2017)
The currant research aimed at deducing science teaching method from The verses) 82-60) of Surah Al-Kahf in the Holly Quran and cognitive equilibrium concept. It also aimed to investigate its effectiveness in developing science cncept and self regulation for seventh class students in Gaza Governorates. The method deduced from the verses of Surah Al-Kahf, consisted of two parts: The first illustrated it's stages. The second part illustrated the conditions of learning within this method. This method was applied to a sample of (83)seventh class students ,divided into two groups: The experimental group, was taught the heat in our life unit by the suggested method ,and control group, was taught the same unit by the traditional method. After applying both science concepts achievement test, and the self regulation scale, results of the study revealed a significant difference between the two groups in both science concepts achievement and self regulation, in favor of the experimental group. The study recomended that it is necessary for science teachers to employ the suggested method in their teaching